Формування продуктивності сої залежно від добрив та біопрепаратів в умовах Центру України - Онищенко, Павло Олександрович; Onyshchenko, Pavlo (ЦНТУ, 2024)
В даній випускній кваліфікаційній роботі вивчено ефективність застосування дорив та біопрепаратів у технології вирощування сої в умовах Центру України. Мета досліджень - встановити ефективність різних видів добрив як в чистому вигляді, так і при сумісному їх використанні з іншими видами добрив при вирощуванні сої в умовах Центру України. Встановлено, що найбільш ефективним в умовах Центру України при вирощуванні сої сорту Тріада є внесення під час сівби стартової дози рідкого комплексного добрива на фоні передпосівної бактеризації насіння бактеріальними препаратами типу Нітроген Т та приорювати післяжнивні рештки після вирощування попередника. This final qualification work studies the effectiveness of the use of fertilizers and biological products in the technology of growing soybeans in the conditions of the Center of Ukraine. The purpose of the research is to establish the effectiveness of different types of fertilizers both in pure form and when used together with other types of fertilizers in growing soybeans in the conditions of the Center of Ukraine. It was established that the most effective in the conditions of the Center of Ukraine when growing soybeans of the Triada variety is the application of a starting dose of liquid complex fertilizer at sowing against the background of pre-sowing bacterization of seeds with bacterial preparations such as Nitrogen T and plowing post-harvest residues after growing the predecessor.
Formation of soybean productivity depending on fertilisers and biological products in the conditions of Centre of Ukraine
Keywords: соя; рідкі комплексні добрива; врожайність; soybean; liquid complex fertilizers, productivity; productivity